Nil(n)-Modules Bifibred over Groups (European Journal of Pure and Applied Mathematics, 2017)
In this work, we defined a functor from category of nil(n)-modules to that of groups. Then we showed by direct calculation that the functor is both fibration and cofibration of categories.